Vertigo as A Manifestation of Cervical Rib: Case Report - Sulistyani, S; Hutami, Norma Putri; Sulistiyo, Azka Hafiy; Prameswari, Elza; Azwar, Muhammad Thoriq; Setiawan, Iwan (Universitas Muhammadiyah Surakarta, 2024)
Background: A cervical rib is a congenital anomaly of a cervical spine vertebra, occurring in about 0.5% to 1% of the population. It is most commonly associated with the seventh cervical vertebra. Cervical ribs can lead to localized pain and affect surrounding structures, presenting with a variety of clinical symptoms. Objective: To demonstrate that a cervical rib can cause vertigo, particularly central vertigo. Case: A 55-year-old woman experienced vertigo and nausea for approximately ten years. Physical examination revealed her head tilted to the left, with an inability to maintain a straight position. Positive cerebellar signs were observed. Imaging studies showed a cervical rib on the seventh cervical vertebra in the X-ray and bilateral cerebellar infarctions in a CT scan. Discussion: The patient, a female, had a cervical rib on the right side. The vertigo was linked to a cerebellar stroke caused by the cervical rib. The underlying mechanism likely involved compression of the subclavian artery and poor posture. Conclusion: Vertigo can be a clinical manifestation of cerebellar stroke, resulting from subclavian artery compression due to a cervical rib.